Human Resource Empowerment and Marketing Development for Coconut Root Snack MSMEs in Jayamulya Village - Giri Nurpribadi; Erina Rulianti (Lentera Ilmu Nusantara, 2026)
This community service activity was conducted in Jayamulya Village, Serang Baru District, Bekasi Regency, with the aim of empowering coconut root snack MSMEs through human resource strengthening, production improvement, marketing development, and business legality support. The method used was participatory community empowerment, which was implemented through observation, discussion, product identification, digital empowerment, and cultural adaptation to the local community context. The activity involved direct observation of the coconut root snack production process, discussions with MSME managers, identification of production tools and packaging needs, and mapping of existing marketing networks. The results showed that coconut root snack MSMEs have promising potential to support household income and village economic development. However, several aspects still need improvement, including production process standardization, product packaging, market expansion, digital marketing utilization, and business legality. Digital empowerment was introduced as an opportunity to expand promotion and distribution through online marketing channels. In addition, assistance related to NIB and P-IRT registration was identified as an important step to strengthen product legality, labeling, and consumer trust. Therefore, continuous assistance from universities, local government, and related stakeholders is needed to improve the competitiveness and sustainability of coconut root snack MSMEs in Jayamulya Village.